Upaya Mereduksi Miskonsepsi Literasi Melalui Pendampingan Produksi Konten Booktube Bagi Peserta Didik SMP Negeri 3 Batang - Santi Pratiwi Tri Utami; Usrek Tani Utina; Moh. Iqbal Mabruri; Restu Aditia (Bahasa Indonesia, 2022)
Abstract The implementation of the School Literacy Movement (GLS) at SMP Negeri 3 Batang challenges is interpreted as reading activities. This shows the existence of literacy misconceptions. The main obstacle encountered was the absence of a follow-up program from the GLS. Team's study formulated a solution, namely a post-reading follow-up mentoring program in the form of Booktube (Book Reviews on Youtube). The formulation of the problem in this service activity is 1) what efforts are being made to reduce misconceptions at SMP Negeri 3 Batang?, and 2) how is the implementation of Booktube production assistance at SMP Negeri 3 Batang? This activity was held on August 4, September 2, and September 21, 2021 with 76 students. The results of the activity, namely 1) Efforts made to reduce literacy misconceptions are knowing the post-reading mentoring program in the form of Booktube, 2) Implementation of Booktube production assistance through training in writing interesting book reviews, production of Booktube content, and ends with the practice of producing and uploading book review content on Youtube. The results of this service activity are optimal in an effort to reduce misconceptions with the follow-up of the GLS in the form of a production of 57 Booktubes. Abstrak Implementasi Gerakan Literasi Sekolah (GLS) di SMP Negeri 3 Batang sekadar dimaknai sebagai kegiatan membaca selama 15 menit sebelum pembelajaran. Hal tersebut menunjukkan adanya miskonsepsi literasi. Kendala utama yang ditemui ialah belum adanya program tindak lanjut dari GLS. Hasil telaah tim merumuskan solusi berdasarkan kondisi mitra, yaitu pendampingan program tindak lanjut pascabaca berupa produksi konten Booktube (Book Review on Youtube). Perumusan masalah dalam kegiatan pengabdian ini ialah 1) apa upaya yang dilakukan untuk mereduksi miskonsepsi program literasi sekolah di SMP Negeri 3 Batang?, dan 2) bagaimanakah implementasi pendampingan produksi Booktube di SMP Negeri 3 Batang? Kegiatan ini dilaksanakan pada tanggal 4 Agustus, 2 September, dan 21 September 2021 bersama 76 peserta didik. Rincian hasil kegiatan, yakni 1) Upaya yang dilakukan untuk mereduksi miskonsepsi literasi di SMP Negeri 3 Batang ialah dengan pendampingan program tindak lanjut pascabaca berupa produksi konten Booktube, 2) Implementasi pendampingan produksi Booktube di SMP Negeri 3 Batang melalui pelatihan menulis review buku yang menarik, pelatihan produksi konten Booktube, dan diakhiri dengan praktik memproduksi dan mengunggah konten review buku di Youtube. Hasil kegiatan pengabdian ini optimal dalam upaya mereduksi miskonsepsi program literasi sekolah di SMP Negeri 3 Batang dengan adanya tindak lanjut GLS berupa produksi sejumlah 57 Booktube.